Anisotropic optical film embedded with cellulose nanowhisker. (5th October 2015) - Kim, Dah Hee; Song, Young Seok
Highlights: Anisotropic optical behaviors of composite films embedded with CNWs were investigated. Elongation was applied to the composite film in order to control the orientation of CNWs. Aligned CNWs yield remarkable anisotropic microstructure and optical properties. Abstract: We investigated anisotropic optical behaviors of composite films embedded with CNWs. To control the orientation of CNWs, elongation was applied to the composite film. Morphological and mechanical analyses of the specimens were carried out to examine the influence of the applied extension. The CNWs were found to be aligned in the elongated direction, yielding remarkable anisotropic microstructure and optical properties. As the applied elongation and CNW loading increased, the resulting degree of polarization and birefringence increased due to increased interactions between the embedded particles. This study suggests a way to prepare an anisotropic optical component with nanoparticles of which the microstructures, such as orientation and filler content, can be controlled.